Economics of Harvesting and Threshing of Wheat and Paddy in Northern India - Ahuja, S S; Rikhi, Pramod; Dogra, Baldev (Journal of Agricultural Engineering, 2007)
Harvesting and threshing of wheat and paddy is the major labour intensive farm operation. Migratory labour normally from UP and Bihar has been involved. However, combining has been introduced on large scale in Northern India. Combining intensity for wheat and paddy crops worked out to be 43.05 and 58.07 per cent respectively for the Northern India. Combine harvested wheat fields require clearing of the field by use ofstraw combines, whereas paddy straw is normally burnt except in case of basmati varieties.